Transmission of mycoviruses: new possibilities - Buivydaitė, Živilė; Winding, Anne; Sapkota, Rumakanta (Frontiers in Microbiology, 2024)
Mycoviruses are viruses that infect fungi. In recent years, an increasing number of mycoviruses have been reported in a wide array of fungi. With the growing interest of scientists and society in reducing the use of agrochemicals, the debate about mycoviruses as an effective nextgeneration biocontrol has regained momentum. Mycoviruses can have profound effects on the host phenotype, although most viruses have neutral or no effect. We speculate that understanding multiple transmission modes of mycoviruses is central to unraveling the viral ecology and their function in regulating fungal populations. Unlike plant virus transmission via vegetative plant parts, seeds, pollen, or vectors, a widely held view is that mycoviruses are transmitted via vertical routes and only under special circumstances horizontally via hyphal contact depending on the vegetative compatibility groups (i.e., the ability of different fungal strains to undergo hyphal fusion). However, this view has been challenged over the past decades, as new possible transmission routes of mycoviruses are beginning to unravel. In this perspective, we discuss emerging studies with evidence suggesting that such novel routes of mycovirus transmission exist and are pertinent to understanding the full picture of mycovirus ecology and evolution.